2013
DOI: 10.1007/s11418-013-0803-y
|View full text |Cite
|
Sign up to set email alerts
|

Three acetophenones from Acronychia pedunculata

Abstract: Phytochemical investigation of the leaves and twigs of Acronychia pedunculata has led to the isolation of three new acetophenone monomers 1-3 as well as 1-[2',4'-dihydroxy-3',5'-di-(3″-methyl-2″-butenyl)-6'-methoxy]phenylethanone (4), acronyculatin E (5), a mixture of β-sitosterol and stigmasterol, and sesamin. The structures of these new compounds were elucidated spectroscopically. The inhibitory activities of the isolated acetophenone derivatives against mammalian DNA polymerases and human cancer cell growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…The 13 C NMR data of 1 (Table 1) revealed 19 signals, including those of a ketocarbonyl ( δ C 203.3), a pair of olefinic carbons ( δ C 131.4 and 122.2), six aromatic carbons ( δ C 161.1, 159.7, 157.4, 113.2, 109.3, and 104.3), an oxygenated tertiary carbon ( δ C 77.8), and an oxymethine ( δ C 69.2). These data resembled those of the known acronyculatin G ( 10 ), 5 which was also isolated in this study, except for the C-1″ benzylic methylene and C-2″ oxymethine in 1 instead of an olefinic moiety in 10 . The 2D NMR experiments, including H–H COSY, HMQC, and HMBC, revealed the presence of a benzene moiety fully substituted with an acetyl, a hydroxy, a prenyl, a methoxy, and a 2,3-dioxygenated 2-methylbutane moiety (Figure 2).…”
Section: Resultssupporting
confidence: 87%
“…The 13 C NMR data of 1 (Table 1) revealed 19 signals, including those of a ketocarbonyl ( δ C 203.3), a pair of olefinic carbons ( δ C 131.4 and 122.2), six aromatic carbons ( δ C 161.1, 159.7, 157.4, 113.2, 109.3, and 104.3), an oxygenated tertiary carbon ( δ C 77.8), and an oxymethine ( δ C 69.2). These data resembled those of the known acronyculatin G ( 10 ), 5 which was also isolated in this study, except for the C-1″ benzylic methylene and C-2″ oxymethine in 1 instead of an olefinic moiety in 10 . The 2D NMR experiments, including H–H COSY, HMQC, and HMBC, revealed the presence of a benzene moiety fully substituted with an acetyl, a hydroxy, a prenyl, a methoxy, and a 2,3-dioxygenated 2-methylbutane moiety (Figure 2).…”
Section: Resultssupporting
confidence: 87%
“…The structures of the known compounds (6e10, 12 and 15e24) were identified by means of spectroscopic analyses (ESIMS, 1 H and 13 C NMR) and by comparing the spectroscopic data with literature values of the following compounds: 3,5-di-C-b-D-glucopyranosyl phloroacetophenone (6) (Sato et al, 2004), kaempferol 3-robinobioside (7) (Brasseur and Angenot, 1986), kaempferol 3-Ob-D-glucopyranosyl (1 / 2)-a-D-xylopyranoside (8) (Fiorentino et al, 2009), icariside B 5 (9) (Matsunami et al, 2010), tamarixetin 3-robinobioside (10) (Barrero et al, 1998), leptonol (12) (Li and Zhu, 1998), 8-acetyl-7-hydroxy-5,6-dimethoxy-2,2-dimethyl-2H-l-benzopyran (15) (Kamperdick et al, 1997), evodione (16) (Kamperdick et al, 1997), leptene A (17) (Guo-Lin et al, 1997), isoevodionol (18) (Li and Zhu, 1999), 6-acetyl-7-hydroxy-5-methoxy-2,2-dimethyl-2H-chromene (19) (Donnelly et al, 1995), 6-(1-methoxyethyl)-5,7,8-trimethoxy-2,2-dimethyl-2H-l-benzopyran (20) (Kamperdick et al, 1997), acronyculatin G (21) (Kozaki et al, 2014), 6-(lhydroxyethyl)-5,7,8-trimethoxy-2,2-dimethyl-2H-1-benzopyran (22) (Kamperdick et al, 1997), 3,5,4 0 -trihydroxy-8,3 0 -dimethoxy-7-(3-methylbut-2-enyloxy)flavone (23) (Sultana et al, 1999), and 3,5,3 0 -trihydroxy-8,4 0 -dimethoxy-7-(3-methylbut-2-enyloxy) flavone (24) (Xie et al, 2011b).…”
Section: Resultsmentioning
confidence: 99%
“…(Rutaceae) is a small evergreen plant widely distributed from East Asia to South Asia, including South China, India, Sri Lanka and Indonesia. Extracts of the leaves, bark, stems and fruits of this plant are widely used in folk medicine to treat scabies, sores and ulcers, [5] and are reported to have antimicrobial activity, [6] cytotoxicity [7][8][9][10] and antioxidant capacity. [11] Various compounds have been isolated and identified from A. pedunculata, including quinolone alkaloids [12] and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] We previously reported the new acetophenones acrophenone A, B and C and several known acetophenone dimer compounds, [15] such as acrovestenol and acrovestone. Previous reports [9,11,[16][17][18] have indicated that the biological activities of acetophenone monomers are low. Our experiments have also shown that the acetophenone monomers prenylacronylin and acronylin, which are predicted to be components in acetophenone dimers, have cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%